Topographical Organization of the Pedunculopontine Nucleus - Martinez-Gonzalez, Cristina; Bolam, J P.; Mena-Segovia, Juan (Frontiers in Neuroanatomy, 2011)
Neurons in the pedunculopontine nucleus (PPN) exhibit a wide heterogeneity in terms of their neurochemical nature, their discharge properties, and their connectivity. Such characteristics are reflected in their functional properties and the behaviors in which they are involved, ranging from motor to cognitive functions, and the regulation of brain states. A clue to understand this functional versatility arises from the internal organization of the PPN. Thus, two main areas of the PPN have been described, the rostral and the caudal, which display remarkable differences in terms of the distribution of neurons with similar phenotype and the projections that originate from them. Here we review these differences with the premise that in order to understand the function of the PPN it is necessary to understand its intricate connectivity. We support the case that the PPN should not be considered as a homogeneous structure and conclude that the differences between rostral and caudal PPN, along with their intrinsic connectivity, may underlie the basis of its complexity.